Stabilization and Environmental Sustainability of Swelling Clays Soils: A Review - Oziegbe, Ehitua Julius; Oziegbe, Olubukola (Covenant Journal of Physical and Life Sciences, 2025)
Water movement in swelling soils conforms with material continuity. This invariably justifies the differences in the gravitational potential energy during expansion and the anisotropic stresses that press the soil but allow for vertical movement. Under fluid conditions, vane efficiency exhibited by macropores is lowered by swelling of the clay, and a poorly drained soil results in surface saturation. The type of water applied to soil material tends to have an impact on the positioning of cracks in swelling clays, and thus, cracks can remain pathways for preferential flow much after they are covered at the soil surface. Over time, chemicals and chemical compounds have been utilized to further enhance the engineering properties of such soils. However, environmentally friendly biodegradable biological stabilizers are taking the place of conventional stabilizers, most especially lime and cement. Additionally, biochar amendment, which is ecofriendly, has also been found to lower the swelling index capability of expansive clay soil. Despite the dangers associated with swelling clay, it has found extensive use as adsorbents, carriers in drug delivery systems, and the building of a storage tank for the disposal of radioactive materials. In addition, swelling clays have found significant usage in the production of controlled-release fertilizers (CRFs) formulations. Hence this paper emphasizes the environmental impact of building large structures and road construction on swelling clay soils, highlights recent progress in the inhibition and stabilization of swelling soils to sustain the environment, and enumerates the economic importance associated with swelling clay soils.